Disentangling the Effects of Health Reform in Massachusetts: How Important Are the Special Provisions for Young Adults? - Long, Sharon K; Yemane, Alshadye; Stockley, Karen (American Economic Review, 2010)
Disentangling the Effects of Health Reform in Massachusetts: How Important Are the Special Provisions for Young Adults? by Sharon K. Long, Alshadye Yemane and Karen Stockley. Published in volume 100, issue 2, pages 297-302 of American Economic Review, May 2010